Chemical composition and in vitro antioxidant and antibacterial activities of sargassum vulgare c. agardh from Lobo, Batangas, Philippines - Arguelles, Eldrin DLR.; Monsalud, Rosario G.; Sapin, Arsenia B. (2019)
Seaweeds are notable in producing diverse kinds of bioactive compounds with promising pharmacological properties. A study was conducted at the National Institute of Molecular Biology and Biotechnology (BIOTECH), University of the Philippines Los Banos from July to November 2018 to evaluate the proximate composition and potential antioxidant and antibacterial properties of a brown macroalga, Sargassum vulgare C. Agardh.